Analisis Morfologi dan Imaji Puitis dalam Puisi “’Alā Al-Ghaym” Karya Nizār Qabbānī - Khairunni'ma, Khairunni'ma; Ekawati, Ekawati; Kamal, Muhammad Badrul; Kusuma, Aldi Wijaya; Batubara, Ulfa Angriaini (Study Program of Arabic Language Teaching, 2026)
This research examines the structural characteristics and poetic imagery in Nizār Qabbānī’s poem ʿAlā al-Ghaym, aiming to clarify their roles and forms in shaping both aesthetic and emotional interpretations. The study specifically intends to (1) outline the prevalent morphological structures utilized in the poem and (2) explore the different kinds and purposes of poetic imagery, focusing on tashbīh and majāz mursal, within a stylistic context. The methodology employed in this study is qualitative descriptive with a stylistic lens. A qualitative approach is selected because the information consists of linguistic components and figurative language found in a literary work rather than numerical statistics. The stylistic perspective is applied to analyze how language selections operate artistically and convey meaning in poetry. The materials for this investigation include lines from Nizār Qabbānī's poem ʿAlā al-Ghaym. The main source of data is the version of the poem published in al-Aʿmāl al-Shiʿriyyah al-Kāmilah, while additional information is drawn from books, journal publications, and earlier research on Arabic stylistics, morphology (ṣarf), and Arabic rhetoric (balāghah). Data collection was conducted through intensive reading and documentation. The poem was thoroughly examined to pinpoint linguistic aspects relevant to the research objectives, with the chosen data documented and categorized according to morphological classifications and types of poetic imagery. Data analysis employed a descriptive qualitative content analysis approach. The analysis involved identifying various morphological forms, such as fiʿl, ism, ḍamīr, and wazan, as well as instances of poetic imagery, including tashbīh and majāz mursal. The results were then interpreted using the principles of Arabic stylistics to clarify their aesthetic, emotional, and semantic roles within the poem.